Adjuvant intra-arterial chemotherapy for patients with resected colorectal liver metastases: a systematic review and meta-analysis. Issue 3 (March 2022) - Buisman, Florian E.; Filipe, Wills F.; Galjart, Boris; Grünhagen, Dirk J.; Homs, Marjolein Y.V.; Moelker, Adriaan; Verhoef, Cornelis; Groot Koerkamp, Bas
Abstract: Background: The practice of adjuvant hepatic arterial infusion chemotherapy (HAIC) for colorectal liver metastasis (CRLM) varies widely. This meta-analysis investigates the effectiveness of adjuvant HAIC and the influence of variations in HAIC treatment in patients with resected CRLM. Methods: PRISMA guidelines were followed for this study. The search was limited to comparative studies (HAIC vs non-HAIC) for overall survival. Subgroup meta-analyses using random-effects were performed for type of intra-arterial drug, method of catheter insertion, use of concomitant adjuvant systemic chemotherapy, and study design. Results: Eighteen eligible studies were identified. After excluding overlapping cohorts, fifteen studies were included in the quantitative analysis, corresponding to 3584 patients. HAIC was associated with an improved overall survival (pooled hazard ratio (HR) 0.77; 95%CI 0.64–0.93). Survival benefit of HAIC was most pronounced in studies using floxuridine (HR 0.76; 95%CI: 0.62–0.94), surgical catheter insertion with subcutaneous pump (HR 0.71; 95%CI: 0.61–0.84), and concomitant adjuvant systemic chemotherapy (HR 0.75; 95%CI: 0.59–0.96). The pooled HR of RCTs was 0.91 (95%CI 0.72–1.14), of which only 3 used floxuridine. Conclusion: Adjuvant HAIC is a promising treatment for patients with resectable CRLM, in particular HAIC with floxuridine using a surgically placed catheter and a subcutaneous pump, and concomitant systemic chemotherapy.